How is the following equation possible?

\[ x^3 - 6x - 40 = (x-4)(x^2+4x+10) \]

I forgot

How is the following equation possible?

\[ x^3 - 6x - 40 = (x-4)(x^2+4x+10) \]

I forgot

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewest\(x^3-6x-40 \\ = x^3-4x^2+4x^2-16x+10x-40 \\ = x^2(x-4)+4x(x-4)+10(x-4) \\ = (x-4)(x^2+4x+10)\)

Its not something to memorize to forget though :P

Log in to reply

Thanks Nihar, it was quite helpful.

Log in to reply

\( x^3 - 6x - 40 \\ = x^3 \color{red}{- 4x^2 + 4x^2 - 16x + 10x} - 40 \)

How did you get those red numbers ?

Log in to reply

So that we can factor out \((x-4)\) from each pair.

Log in to reply

Log in to reply

I'm felling silly now XD

I'm 13

Log in to reply